THE ART OF EMBROIDERY DECORATION OF SEWING ITEMS WITH EMBROIDERY METHOD - Yakubova Marhabo Yusufovna; Zaripova Umida Nig'monjon qizi (Bright Mind Publishing, 2025)
This article discusses the art of gold embroidery and its role in decorating sewing items. Gold embroidery is a unique national craft, the art of embroidering fabric with gold and silver threads, as well as pearls, stones and other decorative elements. This technique gives dresses, curtains, bags and other fabric items an elegant and rich look. The article provides detailed information about the history, main methods and importance of gold embroidery in modern sewing.
Keywords: Gold embroidery, crafts, sewing items, gold embroidery methods, national ornament, gold and silver threads, patterns and decorations, embroidering fabric is a traditional craft.